Cultural conflict in Ian McEwan’s On Chesil Beach through semiotics - Abbasiyannejad, Mina; Talif, Rosli (Universiti Putra Malaysia Press, 2013)
Contemporary British writer Ian McEwan explored various themes as he progressed from his early fiction to his later work, focusing more on personal relationships in the later years and how such relationships were affected by cultural and other issues of the time. He also shows how the macrocosm, which is society, affects the microcosm (human relationships) directly or indirectly. His meticulous writing style is obvious in all of his works. McEwan’s careful choice of words and use of similes, metaphors and symbols creates diverse moods and touches the very emotional and psychological core of the reader. On Chesil Beach is an excellent example of his craft, as he presents the reader with conflicts at various levels. The protagonists, Edward and Florence, suffer the burden of belonging to different social classes; challenged by the constraints of Victorian-era sexual boundaries while facing the consequences of a lack of proper communication and miscommunication. Edward and Florence, like most of the major characters of McEwan’s later novels, are victims of their time and this paper strives to understand, and interpret the signs by using semiotics as a tool to unravel the meaning behind the words.